Al-Hikmah Al-Muta'aliyah: The Synthesis of Mulla Sadra's Islamic Philosophy and Its Influence on Islamic Epistemology - Avita Aniqotul 'Athiyyah; Achmad Khudori Soleh; Nanda Azzah Salsabila (Aqlania, 2025)
Al-Hikmah al-Muta'aliyah holds its significance in the harmonious integration of philosophy, mysticism, and Islamic theology. This study aims to uncover the concept of al-Hikmah al-Muta'aliyah, focusing on its epistemological sources, the methods of acquiring its knowledge, and its verification through its influence on Islamic epistemology. The research employs a descriptive approach in the form of qualitative analysis, utilizing library research and data analysis techniques such as data reading, data presentation, and conclusion drawing. The findings of the study reveal the following: 1) Al-Hikmah al-Muta'aliyah according to Mulla Sadra is a synthesis of prior epistemologies, derived from three principles: intellectual intuition, rational demonstration, and Sharia, forming a wisdom acquired through spiritual enlightenment, presented in rational arguments, and realized by adhering to Sharia regulations. 2) The methods of acquiring it can be achieved in two ways: first, through intellectual intuition and rapid progress, such as direct divine teaching referred to as ‘ilm ladunni (divinely inspired knowledge); and second, through conceptual thought and gradual progress, such as self-learning and following the teachings of a mentor. 3) The verification of Mulla Sadra's epistemological sources is influenced and supported by earlier thinkers, such as Ibn Sina in the field of epistemology, Suhrawardi in the concept of existence and tashkik al-wujud (gradation of existence), and Ibn Arabi in matters of Islamic philosophical issues.